“The Power of Humorous Advertisements on Customer’s Buying Behaviour with Special Reference to Kerala” - Priyanka Harikumar, Girish S (International Journal of Advanced Science and Technology, 2020)
Advertisement is a vital mode employed by corporate to make their products reach the ultimate customers. It is the most effective way to communicate to the customers. It plays an important role in influencing the customers. Corporate use various types of advertisements like, emotional advertisement, humorous advertisement, informative advertisement etc. Humour evokes a positive emotion like laughter. However different people have different perspective on humour. Some like improvisational, whereas some prefer topical and it goes on. Therefore humour should be treated with kid gloves. This study focuses on the various factors of humorous advertisements and the perception of customers towards it. Also this study shows how humorous advertisements influence the purchase decision of the customers. A sample size of 87 respondents was taken for conducting the study. For the purpose of analysis and interpretation, One way ANOVA and Chi-Square was used. It was found that humorous advertisements helps the customers in identifying the brand easily. The concept of the advertisement plays an important role in attracting the viewers. Keywords: Humorous advertisement, positive impact, emotional advertisement, corporate entities